Doing research in fashion and dress : an introduction to qualitative methods - Kawamura, Yuniya, 1963- (Oxford : Berg, 2011)
This text provides readers with a guided introduction to the key qualitative methodological approaches and shows students how'to do' research by combining theoretical and practical perspectives.
Includes bibliographical references (p. [133]-145) and index.
Keywords: Fashion -- Research; Qualitative research; Fashion -- Research -- Case studies; Qualitative research -- Case studies